Thermocatalytic production of Synthetic Natural Gas from renewable carbon dioxide and hydrogen in a fluidized bed reactor with bifunctional solids - Toledo León, Ramsel; Peña, José Ángel; Herguido, Javier; Durán, Paúl (Jornada de Jóvenes Investigadores del I3A, 2025)
In a fluidized bed reactor, the Sabatier reaction was carried out, using a bimetallic Ni/Fe catalyst supported by g-Al2O3 and zeolite 13X as water adsorbent. The objective is to study the methane yield of a mixture made up of CO2 (such as that present in a biogas) and renewable hydrogen; that is, the production of Synthetic Natural Gas (SNG) or Renewable Gas (RNG). This product is also known as Biomethane.